2023
DOI: 10.3389/fneur.2023.1131250
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and the risk of gastrointestinal disorders: A Mendelian randomization study

Abstract: BackgroundThe issue of whether a stroke is causally related to gastrointestinal disorders was still not satisfactorily understood. Therefore, we investigated if there is a connection between stroke and the most prevalent gastrointestinal disorders, including peptic ulcer disease (PUD), gastroesophageal reflux disease (GERD), irritable bowel syndrome (IBS), and inflammatory bowel disease (IBD).MethodsWe applied two-sample Mendelian randomization to investigate relationships with gastrointestinal disorders. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Although this study provides a detailed assessment of the causal relationship between GERD and multiple CVDs, including any stroke, IS and ICH, and numerous CVD risk factors, it was not able to further analyze the causal relationship between GERD and various common subtypes of IS, and the causal association between stroke and its subtypes and GERD risk. Another previous MR study evaluated the causal relationship between stroke and gastrointestinal diseases, including GERD ( 23 ). This study found that ICH, especially deep ICH, can causally increase the risk of gastrointestinal disorders such as GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study provides a detailed assessment of the causal relationship between GERD and multiple CVDs, including any stroke, IS and ICH, and numerous CVD risk factors, it was not able to further analyze the causal relationship between GERD and various common subtypes of IS, and the causal association between stroke and its subtypes and GERD risk. Another previous MR study evaluated the causal relationship between stroke and gastrointestinal diseases, including GERD ( 23 ). This study found that ICH, especially deep ICH, can causally increase the risk of gastrointestinal disorders such as GERD.…”
Section: Discussionmentioning
confidence: 99%
“…First, a genome-wide significance threshold of P < 5 × 10 − was used for SNP selection [14,15]. Secondly, in order to ensure the independence between the selected SNPs, they are required to have pairwise linkage disequilibrium (LD) r 2 < 0.001 and be at least kb =10000 away from each other [16,17]. Calculate R 2 to measure the proportion of variability.…”
Section: Study Design and Ivs Selectionmentioning
confidence: 99%
“…RE independently increases the risk of stroke and TIA in hospitalized elderly patients with AF [ 35 ]. Moreover, GERD has been reported to be an independent causal risk factor for any stroke (odds ratio 1.19, 95% confidence interval 1.06–1.34) [ 36 ]. Similar findings were reported by another Mendelian randomization study [ 37 ].…”
Section: Do We Need New Scores For a Better Prediction Of Stroke And ...mentioning
confidence: 99%